Evaluation of biological, physical and chemical properties of mineral trioxide aggregate mixed with 4-META/MMA-TBB - Rudra Kaul; Riyaz Farooq; Vibhuti Kaul; Altaf H Malik; Aamir Rashid Purra; Lateef Ahmad (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate the change in physical, chemical and biological properties when mineral trioxide aggregate (MTA) is mixed with a resin 4-methacryloxyethyl trimellitate anhydride (4-META)/methyl methacrylate-tri-n-butyl-borane (MMA)-TBB. Materials and Methods: For biological evaluation MTA was inoculated in Wistar rat's subcutaneous tissue and peripheral tissue response was checked after 72 h, 7 days, 15 days and 30 days. Setting time was evaluated using Gillmore needle. The Ca++ release at the end of 24 h was checked using ethylenediaminetetraacetic acid titration method. For all the trials MTA mixed with water was kept as a control and the ratio of MTA with resin was 1:1 by weight. Results: The biological reaction was verified by two observers and their readings were matched using kappa test and there was an excellent relevance. There was no significant difference in the tissue reaction at the end of 30 days where both the groups seemed to show healing. Setting time of MTA with 4-META/MMA-TBB was coming to a mean of 26 min (approx.), which is almost 6 times lesser than that of MTA with water. After applying t test, the difference in Ca++ release was found significant (P = 0.00), with mean of 0.044 and 0.031 mol/L of MTA with water and MTA with 4-META/MMA-TBB respectively. Conclusion: Under the parameters of this study, this new experimental cement has better handling, physical and chemical properties. Even its subcutaneous tissue reaction is comparable to MTA mixed with water.